Biofertilizer - Talukdar, A. Das; Panda, S. K. (Indian Science Cruiser, 2004)
Entire world population depends on agriculture for food. Agricultural productivity Increases through proper fertilisers. Blo-fertlllsers vis-a vis chemical fertilisers are cheap as well as environment friendly. Functions of different types of blofertlllsers have been defined.